Network Coding aware Routing for Efficient Communication in Mobile Ad-hoc Networks - Prashanthi, V; Suresh Babu, D; V. Guru Rao, C (International Journal of Engineering and Technology, 2018)
Existing approach of routing protocols had only partial support towards energy efficiency. However, none of them had focused on considering network coding aware routing to reduce energy consumption. Majority of the existing solutions in literature to improve the communication performance of MANET has focused on minimum cost routing protocols. There are very less significant studies towards network coding in performing routing in MANET system. Therefore, it is totally unknown how network coding could be used to solve such issues. Throughput in wireless networks can be enhanced with the help of network coding. This approach also increases network lifetime in the cases of devices running on battery, such as wireless sensor nodes. Additionally, network coding achieves a reduction in the number of transmissions needed for transmission of a specific message through the network by making energy usage more efficient. Despite its benefits, however, network coding can have a negative impact on network lifetime if it is implemented excessively. •Initially, to achieve the goal of improving throughput, reducing energy efficiency by reducing the number of broadcasting transmissions, a network coding model is created in this study and the MANET broadcast based on network coding is improved by the heuristic principle of Ant Colony Optimization. This study proposes the application of a network coding based dominating set approach to traditional routing protocols like adhoc on demand distance vector (AODV) as a solution to this issue.